Tras la diáspora andina. Una construcción epistémica para fortalecer el proceso intercultural de la ciudad de Cali, Colombia (2021)
The city of Cali has been characterized as a powerful reflection of a multiethnic and multicultural development, where history and different migrations have dynamized cultural practices and their ways of seeing the world. To this extent, an Andean world emerges as a product of the Andean diaspora that carries a burden of memory and adaptation for a city that is open to intercultural dialogue. For many years the question about an Andean Cali has been on the minds of its inhabitants and cultural managers. This question has motivated this article, result of a research for a Master’s degree in Intercultural Studies. The Andean is then the culminating consequence of social relations generated by migrants and local people from Cali that gave way to cultural mixtures that we have called intercultural, sustained by a diasporic process.